PENGARUH LINGKUNGAN KERJA, DISIPLIN, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT ISKANDAR INDAH PRINTING TEXTILE SURAKARTA - Dwi Rini Setianingrum, Djumali & Sri Hartono (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This research aims to determine the influence of work environment, discipline, andmotivation simultaneously on employee performance at PT Iskandar Indah PrintingTextile Surakarta. To determine the influence of work environment on employeeperformance at PT Iskandar Indah Printing Textile Surakarta. To determine theinfluence of discipline on employee performance at PT Iskandar Indah Printing TextileSurakart. To determine the influence of motivation on employee performance at PTIskandar Indah Printing Textile Surakarta. The population in this research is allemployees of PT Iskandar Indah Printing Textile Surakarta amounted to 957 employeesand samples amounted 100 respondents. Technique of data analysis used validity test,reliability test, test the assumption classical, t-test, F-test, and the coefficient ofdetermination. Simultaneously work environment, discipline, and motivation havepositive and significant effect to employee performance of PT Iskandar Indah PrintingTextile Surakarta. Using t-test work environment (X1) have positive and significanteffect to employee performance of PT Iskandar Indah Printing Textile Surakarta. Thediscipline variable has a positive and significant effect to the employee's performance ofPT Iskandar Indah Printing Textile Surakarta. Motivation variable have positive andsignificant effect to employee performance of PT Iskandar Indah Printing TextileSurakarta.Keywords: work environment, discipline. motivation, performance of employees.